Association between exposure to health information and mortality: Reduced mortality among women exposed to information via TV programs. (January 2019) - Sato, Koryu; Viswanath, Kasisomayajula; Hayashi, Hana; Ishikawa, Yoshiki; Kondo, Katsunori; Shirai, Kokoro; Kondo, Naoki; Nakagawa, Keisuke; Kawachi, Ichiro
Abstract: Health communication inequality is one of the potential mechanisms linking socioeconomic status (SES) to health disparities. To our knowledge, no previous study has examined the association between exposure to health information and mortality. We analyzed 3-year follow-up cohort data from the Japan Gerontological Evaluation Study (JAGES), involving 8544 males and 9698 females aged 65 years or older, to examine associations between exposure to health information via different types of media and mortality. The baseline survey was conducted from October to December 2013 in 21 municipalities in Japan. Adjusted for health conditions, health behaviors, and other potential confounders, Cox proportional hazards models were used to estimate hazard ratios (HRs) of all-cause mortality. Over a mean of 3.2 years of follow-up, 956 deaths occurred. Among females, receiving health information from TV programs was associated with lower mortality (HR = 0.90; 95% confidence interval [CI] = 0.83, 0.98). By contrast, there were no significant associations among males. Our findings suggest that improving the accuracy of health information delivered via television might be beneficial. Highlights: Older females who were exposed to health information via TV had lower mortality. Health information via TV was not associated with survival among older males. Printed media and the Internet were not associated with survival in both genders. The first study exploring associations of health information via media with survival.